Changes in macular thickness after trabeculectomy with or without adjunctive 5-fluorouracil - Kadziauskienė, Aistė; Strelkauskaitė, Ernesta; Mockevičiūtė, Eglė; Ašoklis, Rimvydas; Lesinskas, Eugenijus; Schmetterer, Leopold (Acta medica Lituanica, 2017)
Conflict of interest. None of the authors have any conflict of interest to declare, financial or otherwise. No financial or other support was received for the study. Background. The  aim of the  study was to assess changes in macular thickness after trabeculectomy in respect to the  use of 5-fluorouracil (5-FU) as well as to analyse possible associations between the  postoperative changes in macular thickness and intraocular pressure (IOP). Materials and methods. The prospective observational study included 106 eyes (100 patients) with glaucoma who underwent trabeculectomy with or without 5-FU. Subsequently 5-FU needling was performed if failure of the  filtrating bleb occurred. Macular thickness and the  IOP were evaluated before, one week, and six months after the surgery. The mean and sectoral macular thickness was assessed using spectral domain optical coherence tomography. Results. The mean (±SD) IOP reduced from 27.71 (±6.88) mmHg at baseline to 18.3  (±8.1)  mmHg one week (p
Keywords: retinal thickness; macula; trabeculectomy; 5-fluoruracil; intraocular pressure